Attività fisica ed idratazione: quando l’acqua non basta - Aragón Vargas, Luis Fernando (2005)
During sports training and games, thermoregulation may be a challenge when environmental conditions are hot and/or humid. In addition, limited opportunities to drink may promote dehydration and exacerbate the thermoregulatory problem. It is clear that general recommendations for hydration are difficult to give. In competitive and professional sports in particular, it is important to use individualized hydration strategies. Recent studies with professional football teams show the type of measurements which can be performed to monitor the responses and assess the individual needs of each athlete. A wide variability is found even among teammates playing under the same environmental conditions.There is more than water in sweat. Sodium losses tend to be high, and need to be replaced through hydration and regular diet. Sodium plays a key role in hydration. Because competitive athletes tend to exercise at high intensities, they use up considerable amounts of carbohydrate for fuel. Providing carbohydrate in the drinks during exercise can meet some of the needs for fuel supply.